Factors contributing to reading comprehension in children with varying degrees of word-level proficiency. Issue 1 (April 2022) - Bell, Nicola; Wheldall, Kevin
The present study was conducted to explore how the relationships between reading comprehension constructs change according to word reading accuracy, as measured in a large convenience sample ( n = 857) of school-aged students (Years 3–6) with reading difficulties. Multiple regression analyses containing interaction variables were conducted, to determine whether word reading accuracy moderated the relationships between the dependent variable (i.e. reading comprehension) and independent variables (i.e. each of vocabulary and nonword reading accuracy). The interaction variable between word reading accuracy and receptive vocabulary was significant, with steeper slopes evident among more skilled readers compared to less skilled readers. Conversely, the interaction variable between word reading accuracy and nonword reading accuracy was also significant, but with steeper slopes evident among the less skilled reader groups. These patterns align with what has been found in typically developing children: as word reading ability improves, reading comprehension depends more so on language comprehension skills than lower-level decoding skills.